Impact of Repeated Questioning on Interviewers: Learning From a Forensic Interview Training Project. Issue 4 (18th May 2016) - Duron, Jacquelynn F.; Cheung, Monit
ABSTRACT: Forensic interviewers have a difficult job with high risk for career burnout and secondary trauma. Few studies have addressed how new forensic interviewers or trainees experience repeated questioning and multiple interviews. This study simulated the process of training new forensic interviewers through the creation of two interview videos in which social work graduate students participated as actors portraying the roles of interviewer and child. These films served as instructional aids preparing graduate social work students for professional child welfare roles while promoting research-based approaches to interviewing children about sexual abuse allegations. Qualitative data from two cohorts of student actors were collected to analyze interviewers' perspectives on repeated questioning and interviews in child sexual abuse cases. Two themes were extracted from the subjects' experiences: "It is emotionally taxing" and "Navigating the interviewer role is unexpectedly complex." Exposure to repeated questions and multiple interviews affected the performance and confidence of the interviewers.